A zirconium silicate toughened rare earth doped zirconia composite ceramic material, a preparation method and application thereof

CN122897681APending Publication Date: 2026-10-13ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611084789.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,氧化锆全瓷义齿材料存在烧结温度高、半透明性不足、美学效果欠佳、粘接性能有限、低温老化隐患,长期处于口腔潮湿、温度交替变化的环境中,其晶体结构可能发生转变,导致材料韧性下降、易脆裂,缩短修复体使用寿命;同时,其加工性能仍有优化空间,在数字化切削、烧结过程中易出现尺寸偏差、表面裂纹等问题,增加加工成本与操作难度,难以完全适配临床多样化修复需求与患者高品质期待

Benefits of technology

[0023]1、本发明制备的硅酸锆增韧稀土掺杂氧化锆复合陶瓷材料不仅具有高的强度和硬度,而且其断裂韧性也得到了很大的提高,从而延长了义齿的使用寿命,更好地满足义齿的使用要求;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897681A_ABST
    Figure CN122897681A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of biological medical materials, in particular to a zirconium silicate toughened rare earth doped zirconia composite ceramic material, a preparation method and application thereof, which comprises zirconium silicate and rare earth doped zirconia, the mass fraction of the zirconium silicate is 4-22 wt.%, the mass fraction of the rare earth doped zirconia is 78-96 wt.%, the mass fraction of rare earth oxide in the rare earth doped zirconia is 4-11 wt.%, and the mass fraction of zirconia is 89-96 wt.%; the problems of how to improve the fracture toughness, crystal structure stability and processability of zirconia full porcelain denture materials and reduce the sintering temperature are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical materials technology, specifically to a zirconium silicate toughened rare earth doped zirconium oxide composite ceramic material, its preparation method, and its application. Background Technology

[0002] Oral health is an important component of overall health, and denture restoration, as a core means of addressing tooth defects and missing teeth, directly affects a patient's chewing function, facial aesthetics, and quality of life. All-ceramic dentures, with their superior aesthetic performance and excellent biocompatibility, have gradually replaced traditional metal dentures as the mainstream choice for clinical restoration.

[0003] Zirconia all-ceramic dentures, with their superior mechanical properties, can effectively withstand the chewing pressure of posterior teeth and reduce the risk of porcelain chipping, making them the mainstream choice for posterior tooth restoration in clinical practice. They are also widely used in implant-supported superstructure restorations. However, zirconia all-ceramic denture materials have drawbacks, including high sintering temperatures, insufficient translucency, suboptimal aesthetics, limited bonding properties, and the risk of low-temperature aging. Prolonged exposure to the moist and temperature-fluctuating environment of the oral cavity can cause changes in their crystal structure, leading to decreased toughness, brittleness, and a shortened lifespan of the restoration. Furthermore, their processing performance still has room for improvement. Dimensional deviations and surface cracks are prone to occur during digital cutting and sintering, increasing processing costs and operational difficulty, making it difficult to fully meet the diverse restorative needs of clinicians and patients' high-quality expectations.

[0004] Currently, the dental healthcare market continues to expand, and the demand for denture restoration is growing, resulting in high operating costs for dental restoration institutions and making it difficult for patients to enjoy cost-effective restoration services.

[0005] In view of the above-mentioned defects, the inventors of this invention have finally obtained this invention after a long period of research and practice. Summary of the Invention

[0006] The purpose of this invention is to solve the problems of improving the fracture toughness, crystal structure stability, and machinability of zirconia all-ceramic denture materials while reducing the sintering temperature, and to provide a zirconium silicate toughened rare earth-doped zirconia composite ceramic material, its preparation method, and its application.

[0007] To achieve the above objectives, this invention discloses a zirconium silicate-toughened rare earth-doped zirconium oxide composite ceramic material, comprising zirconium silicate and rare earth-doped zirconium oxide, wherein the mass fraction of zirconium silicate is 4-22 wt.%, the mass fraction of rare earth-doped zirconium oxide is 78-96 wt.%, the mass fraction of rare earth oxides in the rare earth-doped zirconium oxide is 4-11 wt.%, and the mass fraction of zirconium oxide is 89-96 wt.

[0008] The rare earth oxide is any one or a combination of two of yttrium oxide, ytterbium oxide, gadolinium oxide, and scandium oxide.

[0009] The rare earth-doped zirconium oxide includes tetragonal zirconium oxide and monoclinic zirconium oxide, wherein the mass fraction of the tetragonal zirconium oxide is not less than 92%, and the remainder is monoclinic zirconium oxide.

[0010] This invention also discloses a method for preparing the above-mentioned zirconium silicate toughened rare earth-doped zirconium oxide composite ceramic material, comprising the following steps:

[0011] S1, rare earth-doped zirconium oxide and zirconium silicate are ball-milled together with anhydrous ethanol to obtain a uniformly mixed slurry;

[0012] S2, after drying the slurry obtained in step S1, a uniformly mixed rare earth-doped zirconium oxide and zirconium silicate powder is obtained.

[0013] S3, the rare earth-doped zirconium oxide and zirconium silicate powder obtained in step S2 is dry-pressed into ceramic blanks, and then cold isostatically pressed to obtain rare earth-doped zirconium oxide and zirconium silicate blanks with uniform stress.

[0014] S4, the uniformly stressed rare earth-doped zirconium oxide and zirconium silicate blanks obtained in step S3 are subjected to first-stage sintering and second-stage sintering to finally obtain zirconium silicate toughened rare earth-doped zirconium oxide composite ceramic material.

[0015] In step S1, the grinding balls used in the ball mill are zirconia grinding balls, the ball milling speed is 360-400 r / min, and the ball milling time is 10-12 h.

[0016] In step S2, the drying is carried out in a forced-air drying oven at a temperature of 30-50℃.

[0017] In step S3, the dry pressing conditions are as follows: holding pressure at 12-25 MPa for 90-180 seconds.

[0018] In step S3, the conditions for cold isostatic pressing are as follows: cold isostatic pressing is performed at 180-220 MPa and held for 5-10 minutes.

[0019] In step S4, the first stage sintering conditions are as follows: sintering at 800-950℃ for 3-5 hours; the second stage sintering conditions are as follows: sintering at 1250-1400℃ for 2-3 hours.

[0020] This invention also discloses the application of the above-mentioned zirconium silicate toughened rare earth doped zirconium oxide composite ceramic material in dental prosthesis restoration, dental implants, and bone implant materials.

[0021] The main crystalline phases of rare-earth-doped zirconium oxide in this invention are tetragonal zirconium oxide and a small amount of monoclinic zirconium oxide. Zirconium silicate is a compound with a single tetragonal crystal structure and extremely low oxygen permeability. Both zirconium silicate and rare-earth-doped zirconium oxide possess high fracture toughness. However, a certain number of oxygen vacancies exist in the lattice of rare-earth-doped zirconium oxide. During high-temperature sintering or long-term service, these oxygen vacancies diffuse and migrate, leading to a phase transformation in the crystal structure of rare-earth-doped zirconium oxide, accompanied by volume changes and a decrease in mechanical properties. This invention uniformly disperses zirconium silicate around a rare-earth-doped zirconium oxide matrix, and sintersulates the uniformly dispersed composite powder of zirconium silicate and rare-earth-doped zirconium oxide at a certain temperature to obtain a composite ceramic. The uniform dispersion of zirconium silicate around the rare-earth-doped zirconium oxide matrix reduces the movement of oxygen vacancies in the matrix. On the one hand, this prevents phase transformation in the matrix and abnormal grain growth at high temperatures; on the other hand, zirconium silicate, as a second phase, enhances the fracture toughness of the matrix without reducing its strength. Meanwhile, zirconium silicate has a low melting point, which allows it to act as a sintering aid during the sintering process of composite ceramics, thereby lowering the sintering temperature. Zirconium silicate-rare earth-doped zirconium oxide composite ceramics possess high fracture toughness, high strength, and high-temperature phase stability.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0023] 1. The zirconium silicate toughened rare earth doped zirconium oxide composite ceramic material prepared by this invention not only has high strength and hardness, but also its fracture toughness is greatly improved, thereby extending the service life of dentures and better meeting the requirements of denture use.

[0024] 2. The zirconium silicate toughened rare earth doped zirconium oxide composite ceramic material of the present invention has good machinability and cutting performance, can be digitally cut, and maintains dimensional stability during the high-temperature sintering process after digital cutting;

[0025] 3. The zirconium silicate toughened rare earth doped zirconium oxide composite ceramic material of the present invention has good high-temperature phase stability and maintains good phase stability and high mechanical properties even at high temperatures for a long time.

[0026] 4. The zirconium silicate toughened rare earth doped zirconium oxide composite ceramic material of the present invention has a lower sintering temperature, which is significantly lower than the sintering temperature (1000-1100℃) and final sintering temperature (1450-1580℃) of the current processable zirconium oxide ceramics; the density of the composite ceramic is still higher than 96% at the low sintering temperature, which can effectively reduce the preparation cost.

[0027] 5. The method for preparing zirconium silicate toughened rare earth doped zirconium oxide composite ceramic material of the present invention is convenient, and it has excellent mechanical properties, good digital cutting machinability and high temperature stability, and can be widely used in the repair or replacement of dental prostheses. Attached Figure Description

[0028] Figure 1 The image shows the surface morphology of the YSZ-ZrSiO4 composite ceramic material in Example 1.

[0029] Figure 2 Fracture toughness values ​​of YSZ-ZrSiO4 composite ceramic material after sintering at 1350℃ for different times in Example 1;

[0030] Figure 3 The image shows a tooth crown (left) made by sintering the 88ScSZ-12ZrSiO4 composite ceramic block at 930℃ for 4 hours and then machining it using CAD / CAM, and a real tooth crown (right) made by adding a small amount of staining solution to the surface of the machined tooth crown and then sintering it at 1300℃ for 3 hours.

[0031] Figure 4 The XRD patterns of the ScYSZ-ZrSiO4 composite ceramic material in Example 4 after sintering at 1350℃ for different times are shown.

[0032] Figure 5 The XRD pattern of the YSZ raw material in Comparative Example 2;

[0033] Figure 6 The image shows the XRD pattern of the YSZ-ZrSiO4 composite ceramic in Comparative Example 3. Detailed Implementation

[0034] The above-mentioned and other technical features and advantages of the present invention will be described in more detail below with reference to the accompanying drawings.

[0035] Example 1

[0036] This embodiment provides a 91.3YSZ-8.7ZrSiO4 (wt%) composite ceramic material, wherein YSZ is yttrium-stabilized zirconium oxide with a mass fraction of 8wt%, of which tetragonal t-ZrO2 accounts for 97wt% and monoclinic m-ZrO2 accounts for 3wt%; the average grain sizes of the raw materials YSZ and ZrSiO4 are 40 nm and 55 nm, respectively. The YSZ nanoparticles are prepared by a hydrothermal method, the specific steps of which are as follows: using zirconium nitrate (Zr(NO3)4·5H2O) and yttrium nitrate (Y(NO3)3·6H2O) as raw materials, 460.807 g of Zr(NO3)4·5H2O and 39.193 g of Y(NO3)3·6H2O are weighed, and an appropriate amount of deionized water is added to prepare a solution with a concentration of 0.2 mol / L. After thorough stirring, excess NH3·H2O is added to adjust the pH of the solution. The value was adjusted to 9, and the mixture was stirred evenly to form a precursor solution. The precursor solution was poured into a hydrothermal reactor and hydrothermally reacted at 180 °C for 10 h. After cooling to room temperature, the precipitate was separated and washed three times with anhydrous ethanol and deionized water to obtain the precursor powder. Finally, the powder was calcined at 800 °C for 2.5 h in air to obtain YSZ nanoparticles.

[0037] The preparation steps of composite ceramics are as follows:

[0038] 91.3 g of YSZ and 8.7 g of ZrSiO4 were weighed into a clean zirconia ball mill jar, and 300 g of zirconia grinding balls were added. Anhydrous ethanol was used as the milling medium, and the mixture was milled in a planetary ball mill at 400 r / min for 12 h to obtain a uniformly mixed slurry. The slurry was then dried in a 40℃ forced-air drying oven to obtain a uniformly mixed rare-earth-doped zirconia and zirconium silicate powder. The uniformly mixed YSZ and ZrSiO4 powder was dry-pressed into a ceramic green body using a 30 mm diameter mold at 15 MPa for 120 s. The resulting ceramic green body was then subjected to cold isostatic pressing at 200 MPa for 8 seconds. A uniformly stressed ceramic green body was obtained by cold isostatic pressing. The YSZ-ZrSiO4 green body obtained by cold isostatic pressing was sintered at 950℃ for 4 hours to obtain a machinable YSZ-ZrSiO4 ceramic block. YSZ-ZrSiO4 composite ceramic materials were prepared by sintering the above machinable YSZ-ZrSiO4 ceramic block at different temperatures and for different times, as shown in Table 1. Table 1 shows the phase composition and mechanical properties of 91.3YSZ-8.7ZrSiO4 sintered at different temperatures and times.

[0039] Figure 1 This image shows the surface morphology of the YSZ-ZrSiO4 composite ceramic material. As can be seen from the image, the composite ceramic is relatively dense, with light gray grains distributed along the grain boundaries of the grayish-white grains.

[0040] X-ray diffraction analysis revealed that the YSZ-ZrSiO4 composite ceramic is mainly composed of tetragonal zirconium oxide (t-ZrO2) and zirconium silicate (ZrSiO4) phases, with a small amount of monoclinic zirconium oxide (m-ZrO2). The actual and theoretical densities of the YSZ-ZrSiO4 composite ceramic were calculated using Archimedes' displacement method and X-ray diffraction, showing a density as high as 98%. Vickers hardness and indentation length were measured using a microhardness tester, and the fracture toughness of the composite ceramic was calculated to be 5.26 MPa·m. 1 / 2 The fracture toughness of the YSZ-ZrSiO4 composite ceramic was improved by 70% compared to that without ZrSiO4. The fracture toughness of this YSZ-ZrSiO4 composite ceramic remained above 5.26 MPa·m after sintering at 1350℃ for 25h, 50h, 75h, and 100h. 1 / 2 Even after sintering at 1350℃ for 100 hours, the fracture toughness reached 6.26 MPa·m. 1 / 2 It is 19% higher than the prepared state, such as Figure 2 As shown in the figure. Meanwhile, the phase composition of the YSZ-ZrSiO4 composite ceramic remained unchanged after sintering at 1350℃ for 100 h, indicating good high-temperature phase stability.

[0041] Table 1. Phase composition and mechanical properties of 91.3YSZ-8.7ZrSiO4 sintered at different temperatures and times in Example 1.

[0042]

[0043] Example 2

[0044] This embodiment provides an 88ScSZ-12ZrSiO4 (wt%) composite ceramic material, wherein ScSZ is scandium oxide partially stabilized zirconium oxide with a mass fraction of 5wt%, of which tetragonal t-ZrO2 accounts for 95wt% and monoclinic m-ZrO2 accounts for 5wt%; the average grain sizes of the raw materials ScSZ and ZrSiO4 are 70 nm and 55 nm, respectively. ScSZ nanoparticles are prepared by a hydrothermal method, the specific steps of which are as follows: using zirconium nitrate (Zr(NO3)4·5H2O) and scandium nitrate (Sc(NO3)3·5H2O) as raw materials, 496.495 g of Zr(NO3)4·5H2O and 34.914 g of Sc(NO3)3·5H2O are weighed, and an appropriate amount of deionized water is added to prepare a solution with a concentration of 0.25 mol / L. After stirring thoroughly, excess NH3·H2O is added to adjust the pH value of the solution to 9, and the solution is stirred evenly to form a precursor solution. The precursor solution was poured into a hydrothermal reactor and hydrothermally reacted at 180 °C for 10 h. After cooling to room temperature, the precipitate was separated and washed three times with anhydrous ethanol and deionized water to obtain the precursor powder. Finally, the powder was calcined at 800 °C for 2.5 h in air to obtain ScSZ nanoparticles.

[0045] The difference between this embodiment and Embodiment 1 is that the ScSZ-ZrSiO4 preform obtained by cold isostatic pressing is sintered at 930℃ for 4 hours, and the final ScSZ-ZrSiO4 composite ceramic is sintered at 1300℃ for 3 hours. The other steps are the same as in Embodiment 1.

[0046] X-ray diffraction analysis revealed that the ScSZ-ZrSiO4 composite ceramics after the first and second stages of high-temperature sintering were composed of tetragonal zirconium oxide (t-ZrO2) and zirconium silicate (ZrSiO4) phases, with a small amount of monoclinic zirconium oxide (m-ZrO2), but no Sc2O3 phase. The density of ScSZ-ZrSiO4 was as high as 98.5%. Using a microhardness tester, the Vickers hardness and indentation length were measured, and the fracture toughness of the composite ceramic was calculated to be 4.87 MPa·m. 1 / 2 The three-point bending strength of the ScSZ-ZrSiO4 composite ceramic was tested using a universal testing machine and found to be 1300 MPa. Figure 3 The images show a tooth crown (left) made by CAD / CAM machining of the 88ScSZ-12ZrSiO4 composite ceramic block sintered at 930℃ for 4 hours in Example 2, and a real tooth crown (right) made by adding a small amount of staining solution to the surface of the machined tooth crown and then sintering at 1300℃ for 3 hours. The results show that the ceramic block bisque fired at 930℃ has good machinability, and the tooth crown is in good condition after the final sintering at 1300℃ for 3 hours, with a bright surface and no cracks.

[0047] Example 3

[0048] This embodiment provides a 95YbYSZ-5ZrSiO4 (wt%) composite ceramic material, wherein YbYSZ is 5wt% ytterbium oxide and 5wt% yttrium oxide partially stabilized zirconium oxide, with tetragonal t-ZrO2 accounting for 93wt% and monoclinic m-ZrO2 accounting for 7wt%. The average grain sizes of the raw materials YbYSZ and ZrSiO4 are 200 nm and 150 nm, respectively. The YbYSZ nanoparticles are prepared by a chemical co-precipitation method followed by high-temperature calcination. The specific steps are as follows: using zirconium nitrate (Zr(NO3)4·5H2O), ytterbium nitrate (Yb(NO3)3·5H2O), and yttrium nitrate (Y(NO3)3·6H2O) as raw materials, a certain amount of 313.576 g Zr(NO3)4·5H2O, 11.397 g Yb(NO3)3·5H2O, and 16.962 g Zr(NO3)4·5H2O, 16.962 g Zr(NO3)3·6H2O, and 16.962 g Zr(NO3)4·5H2O, 11.397 g Yb(NO3)3·5H2O, and 16.962 g Zr(NO3)4·5H2O, 16.962 g Zr(NO3)3·6H2O, 16.962 g Zr(NO3)4·5H2O, 11.397 g Yb(NO3)3·5H2O, and 16.962 g Zr(NO3)4·5H2O, 16.962 g Zr(NO3)3·5H2O, 16.962 g Zr( Y(NO3)3·6H2O was dissolved in an appropriate amount of deionized water to prepare a 0.2 mol / L solution. After thorough stirring, excess urea was added to adjust the pH of the solution to 10, resulting in the precipitation of a large amount of white precipitate. The precipitate was separated and washed three times with anhydrous ethanol and deionized water to obtain the precursor powder. Finally, the powder was calcined at 1000 °C for 3 hours in air to obtain YbYSZ nanopowder.

[0049] The preparation steps in this embodiment are the same as those in Example 1.

[0050] The Vickers hardness and indentation length were measured using a microhardness tester, and the fracture toughness of the composite ceramic was calculated to be 4.56 MPa·m. 1 / 2 The three-point bending strength of the YbYSZ-ZrSiO4 composite ceramic was tested using a universal testing machine and found to be 1200 MPa.

[0051] Example 4

[0052] This embodiment provides an 80ScYSZ-20ZrSiO4 (wt%) composite ceramic material, wherein ScYSZ is a partially stabilized zirconium oxide with a mass fraction of 7wt% scandium oxide and 4wt% yttrium oxide, wherein the tetragonal phase t-ZrO2 accounts for 98wt% and the monoclinic phase m-ZrO2 accounts for 2wt%; the average grain sizes of the raw materials ScYSZ and ZrSiO4 are 40 nm and 50 nm, respectively. The ScYSZ nanoparticles are prepared by a hydrothermal method, the specific steps of which are as follows: using zirconium nitrate (Zr(NO3)4·5H2O), scandium nitrate (Sc(NO3)3·5H2O), and yttrium nitrate (Y(NO3)3·6H2O) as raw materials, 310.092 g of Zr(NO3)4·5H2O, 32.586 g of Sc(NO3)3·5H2O, and 13.569 g of Zr(NO3)4·5H2O, 32.586 g of Sc(NO3)3·5H2O, and 13.569 g of Zr(NO3)4·5H2O are weighed. Y(NO3)3·6H2O was dissolved in an appropriate amount of deionized water to prepare a 0.25 mol / L solution. After thorough stirring, excess NH3·H2O was added to adjust the pH of the solution to 9, and the mixture was stirred until homogeneous to form a precursor solution. The precursor solution was poured into a hydrothermal reactor and hydrothermally reacted at 180 °C for 10 h. After cooling to room temperature, the precipitate was separated and washed three times with anhydrous ethanol and deionized water to obtain the precursor powder. Finally, the powder was calcined at 800 °C for 2.5 h in air to obtain ScYSZ nanoparticles.

[0053] The difference between this embodiment and Embodiment 1 is that the ScYSZ-ZrSiO4 preform obtained by cold isostatic pressing is sintered at 900℃ for 4 hours, and the final ScSZ-ZrSiO4 composite ceramic is obtained by sintering at 1250℃ for 3 hours. Other steps are the same as in Embodiment 1.

[0054] The Vickers hardness and indentation length were measured using a microhardness tester, and the fracture toughness of the composite ceramic was calculated to be 5.24 MPa·m. 1 / 2 The three-point bending strength of the ScYSZ-ZrSiO4 composite ceramic was tested using a universal testing machine and found to be 1280 MPa. Figure 4 The images show the XRD patterns of the ScYSZ-ZrSiO4 composite ceramic material after sintering at 1350℃ for different times in this embodiment. The phase composition of this ScYSZ-ZrSiO4 composite ceramic material remained unchanged after sintering at 1350℃ for 25h, 50h, 75h, 100h, and 150h, respectively, demonstrating good high-temperature phase stability.

[0055] Example 5

[0056] This embodiment provides an 85GdSZ-15ZrSiO4 (wt%) composite ceramic material, wherein GdSZ is a 10wt% gadolinium oxide partially stabilized zirconium oxide, of which the tetragonal t-ZrO2 phase accounts for 93wt% and the monoclinic m-ZrO2 phase accounts for 7wt%; the average grain sizes of the raw materials GdSZ and ZrSiO4 are 500 nm and 400 nm, respectively. The GdSZ nanoparticles are prepared by a hydrothermal method, the specific steps of which are as follows: using zirconium nitrate (Zr(NO3)4·5H2O) and gadolinium nitrate (Gd(NO3)3·6H2O) as raw materials, 313.576 g of Zr(NO3)4·5H2O and 24.897 g of Gd(NO3)3·6H2O are weighed, and an appropriate amount of deionized water is added to prepare a 0.5 mol / L solution. After thorough stirring, excess NH3·H2O is added to adjust the pH of the solution. The value was adjusted to 9, and the mixture was stirred evenly to form a precursor solution. The precursor solution was poured into a hydrothermal reactor and hydrothermally reacted at 180 °C for 10 h. After cooling to room temperature, the precipitate was separated and washed three times with anhydrous ethanol and deionized water to obtain the precursor powder. Finally, the powder was calcined at 800 °C for 2.5 h in air to obtain GdSZ nanoparticles.

[0057] The difference between this embodiment and Embodiment 1 is that: during dry pressing, a ceramic green body is formed by holding the pressure at 20 MPa for 180 s, followed by cold isostatic pressing at 220 MPa for 8 min to obtain the GdSZ-ZrSiO4 green body, which is then sintered at 950℃ for 4 h. Finally, the GdSZ-ZrSiO4 composite ceramic is sintered at 1400℃ for 3 h. The other steps are the same as in Embodiment 1.

[0058] The Vickers hardness and indentation length were measured using a microhardness tester, and the fracture toughness of the composite ceramic was calculated to be 4.5 MPa·m. 1 / 2 The three-point bending strength of the GdSZ-ZrSiO4 composite ceramic was tested using a universal testing machine and found to be 1150 MPa.

[0059] Comparative Example 1

[0060] This comparative example provides a 91.3YSZ-8.7ZrSiO4 (wt%) composite ceramic material, wherein YSZ is yttrium-stabilized zirconium oxide with a mass fraction of 8wt%, wherein the tetragonal phase t-ZrO2 accounts for 97wt% and the monoclinic phase m-ZrO2 accounts for 3wt%; the average grain sizes of the raw materials YSZ and ZrSiO4 are 40 nm and 500 nm, respectively.

[0061] The difference between this comparative example and Example 1 is that the average grain sizes of the raw materials YSZ and ZrSiO4 are 40 nm and 500 nm, respectively. The other steps are the same as in Example 1.

[0062] X-ray diffraction analysis revealed that the YSZ-ZrSiO4 composite ceramic is mainly composed of tetragonal zirconium oxide (t-ZrO2) and zirconium silicate (ZrSiO4) phases, with a small amount of monoclinic zirconium oxide (m-ZrO2). The actual and theoretical densities of the YSZ-ZrSiO4 composite ceramic were calculated using Archimedes' displacement method and X-ray diffraction, showing a density as high as 93%. Vickers hardness and indentation length were measured using a microhardness tester, and the fracture toughness of the composite ceramic was calculated to be 2.86 MPa·m. 1 / 2 It has poor mechanical properties.

[0063] Comparative Example 2

[0064] This comparative example provides a 91.3YSZ-8.7ZrSiO4 (wt%) composite ceramic material, wherein YSZ is yttrium-stabilized zirconium oxide with a mass fraction of 16wt%, and the cubic phase accounts for 100wt%; the average grain sizes of the raw materials YSZ and ZrSiO4 are 50 nm and 60 nm, respectively.

[0065] The difference between this comparative example and Example 1 is that the raw material YSZ is composed of a single cubic phase zirconium oxide (c-ZrO2). The other steps are the same as in Example 1.

[0066] X-ray diffraction analysis in this comparative example showed that the YSZ raw material consisted of a single c-ZrO2 phase (see [reference]). Figure 5 After sintering, the YSZ-ZrSiO4 composite ceramic was found to be mainly composed of c-ZrO2 and ZrSiO4 phases. Using a microhardness tester, the Vickers hardness and indentation length were measured, and the fracture toughness of the composite ceramic was calculated to be 1.98 MPa·m. 1 / 2 It has poor mechanical properties.

[0067] Comparative Example 3

[0068] Comparative Example 3 provides a 91.3YSZ-8.7ZrSiO4 (wt%) composite ceramic material, wherein YSZ is 3.5% by mass of yttrium-stabilized zirconium oxide, of which tetragonal zirconium oxide accounts for 75 wt% and monoclinic zirconium oxide accounts for 25%; the average grain sizes of the raw materials YSZ and ZrSiO4 are 70 nm and 60 nm, respectively.

[0069] The difference between this comparative example and Example 1 is that the raw material YSZ consists of 75 wt% tetragonal zirconium oxide and 25% monoclinic zirconium oxide. The grain size in the raw material differs only slightly. All other steps are the same as in Example 1.

[0070] X-ray diffraction analysis of Comparative Example 3 revealed that, in addition to the ZrSiO4 phase, the rare-earth-doped zirconium oxide in the YSZ-ZrSiO4 composite ceramic contained 70 wt% tetragonal zirconium oxide and 30% monoclinic zirconium oxide (see [link to article]). Figure 6 The Vickers hardness and indentation length were measured using a microhardness tester, and the fracture toughness of the composite ceramic was calculated to be 2.27 MPa·m. 1 / 2 It has poor mechanical properties.

[0071] Comparative Example 4

[0072] This comparative example provides an 83.6% ZrO2-4.4% Sc2O3-12% ZrSiO4 (wt%) composite ceramic material. The raw materials used in this comparative example are ZrO2, Sc2O3, and ZrSiO4, with average grain sizes of 40 nm, 40 nm, and 60 nm for ZrO2, Sc2O3, and ZrSiO4, respectively.

[0073] The composite ceramics in this comparative example are chemically identical to those in Example 2. The difference lies in the raw materials used to prepare the composite ceramics. In Example 2, scandium oxide partially stabilized zirconium oxide and zirconium silicate were used, with tetragonal t-ZrO2 accounting for 95 wt% and monoclinic m-ZrO2 accounting for 5 wt%, and no separate Sc2O3 phase present. In contrast, this comparative example uses three compounds: zirconium oxide, scandium oxide, and zirconium silicate. The other steps are the same as in Example 1.

[0074] X-ray diffraction (XRD) analysis of this comparative example revealed that after the first stage of sintering, the composite ceramic was mainly composed of three phases: m-ZrO2, Sc2O3, and ZrSiO4, exhibiting poor machinability. Further high-temperature sintering in the second stage revealed that the composite ceramic was composed of four phases: tetragonal ZrO2, monoclinic ZrO2, ZrSiO4, and a small amount of Sc2O3. Using a microhardness tester, the Vickers hardness and indentation length were measured, and the average fracture toughness of the composite ceramic was calculated to be 1.58 MPa·m. 1 / 2 It has poor mechanical properties.

[0075] Comparative Example 5

[0076] This comparative example provides a 91.3YSZ-8.7ZrSiO4 (wt%) composite ceramic material, wherein YSZ is yttrium-modified zirconium oxide with a mass fraction of 8wt%, wherein the tetragonal phase t-ZrO2 accounts for 97wt% and the monoclinic phase m-ZrO2 accounts for 3wt%; the average grain sizes of the raw materials YSZ and ZrSiO4 are 40 nm and 55 nm, respectively.

[0077] The difference between this comparative example and Example 1 is that the final firing temperature of the 91.3YSZ-8.7ZrSiO4 (wt%) composite ceramic material was selected as 1500℃ for 2.5h. The other steps were the same as in Example 1.

[0078] X-ray diffraction analysis revealed that the 91.3YSZ-8.7ZrSiO4 composite ceramic of Comparative Example 5 was mainly composed of three phases: tetragonal zirconium oxide (t-ZrO2), monoclinic zirconium oxide (m-ZrO2), and cubic zirconium oxide (c-ZrO2). Importantly, obvious cracks were present on the surface of the composite ceramic sample. Vickers hardness and indentation length were measured using a microhardness tester, and the fracture toughness of the composite ceramic was calculated to be 1.43 MPa·m. 1 / 2 It has poor mechanical properties.

[0079] In summary, this invention utilizes the advantages of both zirconium silicate and rare-earth-doped zirconium oxide by employing zirconium silicate to enhance and toughen the composite ceramic. It is not a simple superposition and sintering process. If the sintering temperature is too low (below 1250℃), the rare-earth-doped zirconium oxide-zirconia silicate composite ceramic will not form a ceramic, resulting in no strength or toughness. If the sintering temperature is too high (above 1500℃), the zirconium silicate in the composite ceramic will first decompose to form zirconium oxide and silicon dioxide. Subsequently, the decomposition products will dissolve into the rare-earth-doped zirconium oxide lattice at high temperatures, resulting in the absence of a zirconium silicate phase in the composite ceramic. Furthermore, sintering at excessively high temperatures can lead to abnormal grain growth and even phase transformation of the rare-earth-doped zirconium oxide, causing a decrease in mechanical properties. Therefore, to achieve high strength, fracture toughness, and good high-temperature phase stability in the zirconium silicate-rare-earth-doped zirconium oxide composite ceramic, a suitable sintering temperature must be selected. In addition, the selection of experimental raw materials is also crucial to the final phase and mechanical properties of the composite ceramic. For example, if zirconium silicate, rare earth oxides, and zirconium oxide are selected as raw materials to prepare rare earth-doped zirconium oxide-zirconia silicate composite ceramics, after high-temperature sintering, the rare earth oxides cannot be completely dissolved into the zirconium oxide lattice, resulting in an increase in the monoclinic phase content in the composite ceramic material. This leads to a sharp decrease in mechanical properties, especially fracture toughness, and also easily causes crack initiation and propagation, thus affecting the performance.

[0080] The above description is merely a preferred embodiment of the present invention and is illustrative rather than restrictive. Those skilled in the art will understand that many changes, modifications, and even equivalents can be made within the spirit and scope defined by the claims of the present invention, all of which will fall within the protection scope of the present invention.

Claims

1. A zirconium silicate-toughened rare earth-doped zirconium oxide composite ceramic material, characterized in that, It includes zirconium silicate and rare earth-doped zirconium oxide, wherein the mass fraction of zirconium silicate is 4-22 wt.%, the mass fraction of rare earth-doped zirconium oxide is 78-96 wt.%, the mass fraction of rare earth oxide in rare earth-doped zirconium oxide is 4-11 wt.%, and the mass fraction of zirconium oxide is 89-96 wt.

2. The zirconium silicate-toughened rare-earth-doped zirconium oxide composite ceramic material as described in claim 1, characterized in that, The rare earth oxide is any one or a combination of two of yttrium oxide, ytterbium oxide, gadolinium oxide, and scandium oxide.

3. The zirconium silicate-toughened rare-earth-doped zirconium oxide composite ceramic material as described in claim 1, characterized in that, The rare earth-doped zirconium oxide includes tetragonal zirconium oxide and monoclinic zirconium oxide, wherein the mass fraction of the tetragonal zirconium oxide is not less than 92%, and the remainder is monoclinic zirconium oxide.

4. A method for preparing a zirconium silicate-toughened rare-earth-doped zirconium oxide composite ceramic material as described in any one of claims 1 to 3, characterized in that, Includes the following steps: S1, rare earth-doped zirconium oxide and zirconium silicate are ball-milled together with anhydrous ethanol to obtain a uniformly mixed slurry; S2, after drying the slurry obtained in step S1, a uniformly mixed rare earth-doped zirconium oxide and zirconium silicate powder is obtained. S3, the rare earth-doped zirconium oxide and zirconium silicate powder obtained in step S2 is dry-pressed into ceramic blanks, and then cold isostatically pressed to obtain rare earth-doped zirconium oxide and zirconium silicate blanks with uniform stress. S4, the uniformly stressed rare earth-doped zirconium oxide and zirconium silicate blanks obtained in step S3 are subjected to first-stage sintering and second-stage sintering to finally obtain zirconium silicate toughened rare earth-doped zirconium oxide composite ceramic material.

5. The preparation method of a zirconium silicate toughened rare earth-doped zirconium oxide composite ceramic material as described in claim 4, characterized in that, In step S1, the grinding balls used in the ball mill are zirconia grinding balls, the ball milling speed is 360-400 r / min, and the ball milling time is 10-12 h.

6. The preparation method of a zirconium silicate toughened rare earth-doped zirconium oxide composite ceramic material as described in claim 4, characterized in that, In step S2, the drying is carried out in a forced-air drying oven at a temperature of 30-50℃.

7. The preparation method of a zirconium silicate toughened rare earth-doped zirconium oxide composite ceramic material as described in claim 4, characterized in that, In step S3, the dry pressing conditions are as follows: holding pressure at 12-25 MPa for 90-180 seconds.

8. The method for preparing a zirconium silicate-toughened rare-earth-doped zirconium oxide composite ceramic material as described in claim 4, characterized in that, In step S3, the conditions for cold isostatic pressing are as follows: cold isostatic pressing is performed at 180-220 MPa and held for 5-10 minutes.

9. The preparation method of a zirconium silicate toughened rare earth-doped zirconium oxide composite ceramic material as described in claim 4, characterized in that, In step S4, the first stage sintering conditions are as follows: sintering at 800-950℃ for 3-5 hours; the second stage sintering conditions are as follows: sintering at 1250-1400℃ for 2-3 hours.

10. The application of a zirconium silicate toughened rare earth doped zirconium oxide composite ceramic material as described in any one of claims 1 to 3 in dental prosthesis restoration, dental implants, and bone implant materials.